2017
DOI: 10.1007/978-3-319-62009-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs’ Over-optimism During the Early Life Course of the Firm

Abstract: Recent research on cognitive biases in decision making suggests that over-optimism critically influences entrepreneurs' decisions to establish and sustain new firms. This paper looks at entrepreneurs' over-optimism during the early life course of the firm, in order to uncover the dynamics and persistence of over-optimism. We use a representative sample of start-ups in the Netherlands, which we divide into solo selfemployed and employer firms. We find that while there is a persistence of overoptimism for the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Thus, by the late 1980s, scholars came to the conclusion that there was no consistent relationship between personality and entrepreneurship and further arguments based on the trait paradigm were often discredited (e.g., Brockhaus & Horwitz, 1986;Gartner, 1988). Other variables such as, self-efficacy (Wang et al, 2016;Zhao, Siebert and Hills, 2005) and over-optimism (Baron, 1998;Hmieleski and Baron, 2009;Kambourova and Stam, 2017) have been subsequently examined within the entrepreneurship literature as researchers found that personality worked better as a predictor of behaviour when coupled with other factors related to motivations and cognitions (Code & Langan-Foz, 2001;Naffziger, 1995).…”
Section: Personality Theory and Entrepreneurshipmentioning
confidence: 99%
“…Thus, by the late 1980s, scholars came to the conclusion that there was no consistent relationship between personality and entrepreneurship and further arguments based on the trait paradigm were often discredited (e.g., Brockhaus & Horwitz, 1986;Gartner, 1988). Other variables such as, self-efficacy (Wang et al, 2016;Zhao, Siebert and Hills, 2005) and over-optimism (Baron, 1998;Hmieleski and Baron, 2009;Kambourova and Stam, 2017) have been subsequently examined within the entrepreneurship literature as researchers found that personality worked better as a predictor of behaviour when coupled with other factors related to motivations and cognitions (Code & Langan-Foz, 2001;Naffziger, 1995).…”
Section: Personality Theory and Entrepreneurshipmentioning
confidence: 99%
“…Incluso más, dado que el emprendimiento es tanto un proyecto económico como existencial, en el que la conducta de las personas y la decisión de emprender, o de persistir en la actividad empresarial -a veces aún a pesar de malos resultados económicos -, no sólo se ve influido por incentivos tradicionales (Storey, 2011;Kambourova y Stam, 2016). Este rasgo comportamental, distante del "individuo representativo" y del homo economicus "maximizador" y racional, vuelve más complejo el fenómeno y engrosa los elementos "no observables".…”
Section: Oscuridades Relacionadas Con El Emprendimiento Y La Teoría Del Cambiounclassified
“…(2010) compared expectations of entrepreneurs as to the success of their own ventures with their assessment of chances of success of other similar businesses. Verheul and Carree (2008) and Kambourova and Stam (2016) asked respondents retrospectively whether the outcomes of their new venture were worse, in line or better than their initial expectations. However, these techniques did not address the issue of self-reporting bias.…”
Section: Measuring Individual-level Overconfidencementioning
confidence: 99%